¿Constitutional jurisdiction in Cuba? : A necessary approach - Mondelo Tamayo, Jorge Olver (2025)
This article analyses the existence of a constitutional jurisdiction in Cuba, based on the 2019 Constitution of the Republic of Cuba and its implementing regulations. It aims to identify the main characteristics of this constitutional jurisdiction, focusing on the regulation of the Cuban constitutional amparo, and to assess its conception as a guarantee for the protection of constitutional rights. This is a qualitative investigation that employed the theoretical methods of analysis-synthesis, inductive-deductive, and the historical method. Specific methods for legal research, such as the comparative legal and legal exegetical methods, were applied. The most up-to-date literature on the subject was reviewed. The main results include the systematization of the features of the constitutional jurisdiction in Cuba, which facilitated the analysis of its potentialities and shortcomings. It is concluded that, although Cuba has a constitutional jurisdiction with a special process for the protection of constitutional rights in ordinary courts, which constitutes its main potential, it presents serious limitations for citizens' access due to the requirements established for the admission of cases.